Functional Roles of Homologous Recombination and Non-Homologous End Joining in DNA Damage Response and Microevolution in Cryptococcus neoformans - Jung, Kwang-Woo (J Fungi (Basel), 2021)
DNA double-strand breaks (DSBs) are the most deleterious type of DNA lesions because they cause loss of genetic information if not properly repaired. In eukaryotes, homologous recombination (HR) and non-homologous end joining (NHEJ) are required for DSB repair. However, the relationship of HR and NHEJ in DNA damage stress is unknown in the radiation-resistant fungus Cryptococcus neoformans. In this study, we found that the expression levels of HR- and NHEJ-related genes were highly induced in a Rad53–Bdr1 pathway-dependent manner under genotoxic stress. Deletion of RAD51, which is one of the main components in the HR, resulted in growth under diverse types of DNA damage stress, whereas perturbations of KU70 and KU80, which belong to the NHEJ system, did not affect the genotoxic stresses except when bleomycin was used for treatment. Furthermore, deletion of both RAD51 and KU70/80 renders cells susceptible to oxidative stress. Notably, we found that deletion of RAD51 induced a hypermutator phenotype in the fluctuation assay. In contrast to the fluctuation assay, perturbation of KU70 or KU80 induced rapid microevolution similar to that induced by the deletion of RAD51. Collectively, Rad51-mediated HR and Ku70/Ku80-mediated NHEJ regulate the DNA damage response and maintain genome stability.